Z-ligustilide and n-Butylidenephthalide Isolated from the Aerial Parts of Angelica tenuissima Inhibit Lipid Accumulation In Vitro and In Vivo - Lee, Wonseok; Koo, Hye Ryoung; Choi, You-Jin; Choi, Jin Gyu; Oh, Myung Sook; Jin, Xing; Choo, Munki; Park, Sunghyouk; Jeong, Yoo-Seong; Chung, Suk-Jae; Lee, Byung-Hoon (Planta Medica, 2019)
Abnormal lipid metabolism, such as increased fatty acid uptake and esterification, is associated with nonalcoholic fatty liver disease (NAFLD). The aqueous extract of the aerial part of Angelica tenuissima Nakai (ATX) inhibited high-fat diet–induced hepatic steatosis in mice as well as oleic acid–induced neutral lipid accumulation in HepG2 cells. ATX decreased the mRNA and protein levels of CD36 and diglyceride acyltransferase 2 (DGAT2), the maturation of sterol regulatory element-binding proteins (SREBP), and the expression of the lipogenic target genes fasn and scd1. The ATX components, Z-ligustilide and n-butylidenephthalide, inhibited the expression of FATP5 and DGAT2 and thus oleic acid–induced lipid accumulation in HepG2 cells. These results suggest that ATX and its active components Z-ligustilide and n-butylidenephthalide inhibit fatty acid uptake and esterification in mice and have potential as therapeutics for NAFLD.
Keywords: Angelica tenuissima Nakai; Apiaceae; lipid metabolism; nonalcoholic fatty liver disease; gene expression